Comparing perceptions of leadership, innovation and performance in Asian SMEs. Issue 4 (8th August 2021) - Muenjohn, Nuttawuth; Ishikawa, Jun; Kongsamutr, Navatasn; Muenjohn, Peamawat; Montague, Alan; Suzumura, Yusuke
ABSTRACT: Having a clear understanding of how leaders perceive their leadership behaviours and firms' situation is critical to help SMEs grasp their strengths and weaknesses. The current paper, therefore, aims to examine the perception towards leadership behaviours, innovation and organizational performance among Asian SMEs. SMEs in China, Japan, Vietnam and Thailand, responded to a survey that revealed their perceptions on four behaviours associated with Design Leadership, four levels of Workplace Innovation, and two types of organizational performance; Profitability and Growth. The analysis of variance was conducted to provide a complete picture of the comparison among the countries. The results revealed that there was a significant difference between Thailand and Japan, Vietnam and Japan, China and Japan on Design Leadership. With relations to Workplace Innovation, there was a negative variance of score between Vietnam and Thailand, and China and Thailand. Finally, significant differences were found amongst most of the countries on Profitability and Growth. The study would assist researchers in understanding how Asian SMEs perceive their leadership behaviours; stages of innovation, and assess their performance. With an accurate perception and understanding, it would lead to the creation of proper strategies and training programs that would contribute to the development of Asian SMEs.